The Trouble with White Feminist Theologians? Decentring White Normativity in Feminist Theology - Galbraith, Eilidh (Feminist theology, 2024)
Feminist theology has provided a critical hermeneutical lens through which to interrogate hegemonic and hierarchical social and theological structures. Yet, can feminist theology itself be charged with the same paradigmatic problems it seeks to challenge? What exactly do we speak of when we speak of feminist theology? More importantly, who are we speaking of? Drawing from Kyla Schuller’s seminal volume, ‘The Trouble with White Women: A counter-history of feminism’, this article seeks to uncover the foundational connections between the historically ‘white feminism’ of Schuller’s counter-history and feminist theology, examining how, and indeed if, feminist theology contests or colludes with this problematic legacy. Considering post-colonial and intersectional feminist perspectives which trouble epistemological normativity, this article asks, is it possible to decentre, from the centre?